A qualitative exploration of nursing students' perceptions of the homeless and their care experiences. Issue 4 (27th June 2018) - Astroth, Kim Schafer; Jenkins, Sheryl Henry; Kerber, Cynthia; Woith, Wendy Mann
Abstract: The health care needs of the homeless are more complex than those of the population at large. The purpose of this qualitative study was to explore undergraduate nursing students' perceptions of the homeless. Thematic content analysis of responses from 19 undergraduate nursing students yielded four themes describing student experiences with the homeless, their perceptions of homelessness and the health care of the homeless, and their suggestions for best teaching strategies. Students in this study had varying amounts of experience with and knowledge of the homeless. While our participants strongly believed that homeless people deserved compassionate, equitable nursing care, many of their statements suggested an implicit bias toward the homeless. This suggests that student nurses need more comprehensive education concerning the homeless and the health care needs of this vulnerable population. Few interventions aimed at educating student nurses about homelessness and changing their attitudes to mitigate bias are based on research, particularly research conducted from the perspective of the homeless, and few explore the impact of civil interactions on health outcomes. The findings of this study may assist nurse educators in developing education interventions to improve students' knowledge of homelessness.